KEPUASAN KERJA KARYAWAN : STUDI LITERATUR - Pitasari, Nimas Ayu Aulia; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2018)
Job   satisfaction   considerably   affects   employee   performance   and   employee outcome.  This  study  aimed  to  present  a  literature  review  of  the  factors  that  affect employee satisfaction conditions and to cover the limitation of previous literature which is being research gaps of this study.Research  method  using  systematic  literature  review.  The  research  data  was obtained through internet search on employee satisfaction journal published 2005-2017 key words using job satisfaction,  employee  satisfaction,  employee  job satisfaction,  job satisfaction,  job  satisfaction  among  employee,  job  satisfaction,  kepuasan  kerja,  and kepuasan kerja karyawan. The number of journals analyzed by 22 journals. Data were analyzed qualitatively.The result of the research is there are six factors that influence job satisfaction that is job content (autonomy and clarity of role), management (performance evaluation and management support), work environment (physical environment, supervisor's relationship  with subordinate,  and co-worker  relationship),  compensation  reward), job promotion  (promotion  and  employment  system),  and  training  (routine  and  effective training).